Ответы и объяснения

Лучший Ответ!
2014-03-20T18:13:45+04:00

778. -x^2 +3x+55=x^2+14x+49
        -2x^2-11x+6=0
         2x^2+11x-6=0
          D= 121 + 4*6*2=169;13
          x1=-11-13/4=-6
          x2=1/2
779. -3x^2 - x +8 = x^2-6x+9
        -4x^2+5x-1=0
         4x^2-5x+1=0
         D= 25-16=9;3
         x1=5-3/8=1/4
         x2=1
780.  x^2-2x+1 -2x^2+6x+31=0
        -x^2+4x+32=0
         x^2-4x-32=0
         D=16+4*32=144;12
         x1=4-12/2=-4
         x2=8
781.   x^2-18x+81 +x^2-15x-50=0
         2x^2-33x+31=0
         D=1089-4*2*31=841;29
         x1=18-29/4=-11/4
          x2=47/4